Emicizumab for hemophilia A with factor VIII inhibitors. Issue 11 (2nd November 2018) - Young, Guy; Callaghan, Michael; Dunn, Amy; Kruse-Jarres, Rebecca; Pipe, Steven
ABSTRACT: Introduction : Hemophilia is a serious bleeding disorder characterized by repeated bleeding episodes into joints and muscles which can lead to permanent disabilities. Treatment with factor replacement therapy has proven to be effective at preventing these complications; however, it can lead to formation of neutralizing antibodies termed inhibitors which significantly complicate the management of the disorder. These inhibitor patients suffer from increased morbidity and mortality and there has been a major unmet need for novel therapeutic approaches. Recently, one such therapy, emicizumab, has been licensed in the United States. Areas covered : This manuscript contains a detailed discussion of the mechanism of action, the clinical trial development program as well as a review of the benefits and risks of this novel agent. In addition, practical considerations for the use of the agent are also described. Expert commentary : Emicizumab represents a new class of medication for the treatment of hemophilia A which in the past has relied on factor replacement therapy and bypassing agent (alternative factor) therapy. Emicizumab fulfills two major unmet needs in patients with hemophilia who have FVIII inhibitors. First, it provides for a much more effective therapy for the prevention of bleeding and second it substantially reduces the treatment burden.